Gill Nets for Inland Fishing in North Kerala - M.P., Remesan; A., Ramachandran (Fishery Technology, 2025)
Results of the study on fishing gear conducted along the inland waters of Kozhikode, Kannur and Kasargod districts of North Kerala during 2003-2004 are reported. The salient features and operational aspects of different types of gill nets in operation are discussed. Most of the gill nets were found to be fabricated with polymide (PA) monofilament of 0.16 mm dia. Gill nets for fish, prawn and crab with mesh size ranging from 12 mm to 220 mm were in use. Trammel nets made of PA mono and multifilament were in operation in some places.